Estimation of Median Lethal Concentration (LC50) of Pyrethroid and Carbamates Pesticides using the Nematode Caenorhabditis elegans to Predict Mammalian Acute Lethality (LD50) - Rana, Krishna; Gautam, Priyanka (Toxicology International, 2023)
Present study was aimed to estimate the median lethal concentration of most extensively used pesticides, pyrethroid (transfluthrin and cyfluthrin) and carbamates’ pesticides (methiocarb and propoxur to deter pests, using a free-living nematode, Caenorhabditis elegans as model organism. The median Lethal Concentration (LC50) was calculated by Log-dose/ probit regression line method, and Worms showed 24-hours lethality at concentrations 37 mg/l, 61 mg/l, 63 mg/l, and 48 mg/l for transfluthrin, cyfluthrin and methiocarb, propoxur respectively on NGM. Structural and toxicidal differences may has been for Differences in the median lethal concentration. LD50 and LC50 values data was compare with mammalian oral LD50 and calculated LC50 using C. elegans respectively. C. elegans found to be the more convenient for generating LC50 values analogous to the mammals LD50 values. So, C. elegans has great promises in the area of toxicological research.